Assessing Vertical Development in Experiential Learning Curriculum. (September 2015) - Spence, Kirsty K.; McDonald, Mark A.
For 30 years, management educators have supported competency-based management education (CBME). When applying CBME, educators stimulate students' lateral development, known as the acquisition of subject-specific knowledge and competencies that deepen their current perceptions and task performance. We contend CBME is necessary but not sufficient to develop future leaders in an increasingly complex world. Concurrently, educators must design curricula to stimulate students' vertical development, described as "how we learn to see the world through new eyes, how we change our interpretations of experience and how we transform our views of reality." This study examines the impact of an 8-month internship course on students' lateral and vertical development. The findings support our contention that experiential learning (EL) curricula developed with both lateral and vertical development components are powerful aids in preparing students to address complex work-related challenges.